THE STUDENT’S SPEAKING CONFIDENCE LEVEL AT LANGUAGE CENTER PARE KEDIRI - Amalia Eka Brilianti (Journal of General Education Science, 2023)
This research aims to describe and analyze the student's speaking confidence level in an English learning environment and deal with Park's theory about four categories of speaking confidence. This research applied the descriptive qualitative method conducted among Academic level students in the Language Centre Kampung Inggris Pare as the participant of this research. The research data were obtained through the speaking confidence test for 12 students in an English learning classroom. Based on the results, the students' speaking confidence level in the English learning environment conducted by the academic level students of Language Center Kampung Inggris Pare were at High and Medium levels. It shows from the test data that 4 out of 12 students got a high level, and 3 out of 12 students got a medium level of speaking confidence in the English learning environment. In addition, the results also show that the percentage of students speaking confidence was 44,4%, remarking a Low level of applying dynamic energy because most students are confident in displaying dynamic energy for their speaking performance. The lowest percentage of students' speaking confidence is 42,7% in the accuracy aspect, which means most students have a low speaking confidence level in the accuracy aspect because they use basic sentence structures and frequently make some errors.